Clinicopathological characteristics and outcome of primary sarcomatoid carcinoma of the gallbladder - Zou, Rui-Qi; Hu, Hai-Jie; Lv, Tian-Run; Liu, Fei; Ma, Wen-Jie; Wang, Jun-Ke; Dai, Yu-Shi; Yang, Si-Qi; Hu, Ya-Fei; Li, Fu-Yu (Frontiers in Oncology, 2022)
Purpose: Our study aims to examine the clinicopathological features, disease progression, management, and outcomes of gallbladder sarcomatoid carcinoma (GBSC) patients. Methods: Between January 2000 and December 2020, 50 gallbladder cancer (GBC) patients who received surgical treatment and were pathologically verified as GBSC at our institution were enrolled. The clinical and pathological features and survival of these patients were retrospectively reviewed. Results: The median overall survival (OS) of GBSC patients was 14.5 months, and the 1-, 2- and 3-year OS rates were 68.0%, 32.0%, and 10.0%, respectively. The median progression-free survival (PFS) was 10.0 months, and the 1-, 2-, and 3-year PFS rates were 42.0%, 16.0%, and 2.0%, respectively. Patients who received radical resection had obviously better OS (18.0 vs. 7.0 months, P<0.001) and PFS (12.0 vs. 5.0 months, P<0.001) than those who underwent palliative resection. Multivariate analysis revealed that vascular invasion (P=0.033), curative operation (P<0.001) and postoperative chemotherapy (P=0.033) were independent risk factors for PFS. We further identified postoperative chemotherapy (P=0.010) and curative operation (P<0.001) as independent prognostic factors affecting the OS of GBSC patients. After curative surgery, patients who underwent S-1-based chemotherapy showed significantly longer recurrence-free survival (RFS) than those who underwent other chemotherapy regimens (20.0 vs 11.0 months, P=0.028). Conclusion: GBSC patients always have aggressive biological behaviors and remarkably poor prognoses. Most GBSC patients are diagnosed in advanced stages, and timely radical operation together with postoperative chemotherapy is important. S-1-based chemotherapy may be a selectively efficient regimen to prolong the survival of GBSC patients.